Low expression of INMT is associated with poor prognosis but favorable immunotherapy response in lung adenocarcinoma - Zhou, Xincheng; Zou, Bing; Wang, Jian; Wu, Lihong; Tan, Qiang; Ji, Chunyu (Frontiers in Genetics, 2022)
Background: The expression of INMT (Indolethylamine N-methyltransferase) has been reported to be downregulated in non-small cell lung cancer (NSCLC). However, the role of INMT in NSCLC remains elusive. We aim to investigate the underlying mechanisms and clinical value of INMT in NSCLC, especially in lung adenocarcinoma (LUAD). Methods: Gene expression cohorts from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) were analyzed to assess the effect of INMT in NSCLC. Gene expression data from an immunotherapy cohort was used to investigate the association of INMT with immunotherapy in NSCLC. Results: INMT expression was significantly downregulated in NSCLC, compared with adjacent normal tissues. Downregulated INMT was associated with poor overall survival in LUAD, but not in lung squamous carcinoma. Multivariate Cox regression analysis suggested that INMT was an independent prognostic marker in LUAD. INMT had a reference value in the diagnosis and prognostic estimation of LUAD. Gene set enrichment analysis showed that pathways of the cell cycle and DNA damage response were enriched in INMT low expression group. The top ten hub genes upregulated in INMT low expression group mainly activated the cell cycle pathway. In addition, more frequently mutated TP53 genes, and higher aneuploidy scores, fraction of genome altered, MANTIS scores, and tumor mutation burden were found in tumors with INMT low expression. Furthermore, patients with low expression of INMT showed favorable clinical benefits to anti-PD-1 treatment with higher enrichment scores of immune-related signatures. Conclusion: Low expression of INMT was associated with poor prognosis but favorable immunotherapy response in LUAD. INMT may affect the progression of LUAD by regulating the cell cycle and may serve as a valuable independent prognostic biomarker in patients with LUAD.